Isocyanide Multicomponent Reactions on Solid Phase: State of the Art and Future Application - Cankařová, Naděžda; Krchňák, Viktor (International journal of molecular sciences, 2020)
Drug discovery efforts largely depend on access to structural diversity. Multicomponent reactions allow for time-efficient chemical transformations and provide advanced intermediates with three or four points of diversification for further expansion to a structural variety of organic molecules. This review is aimed at solid-phase syntheses of small molecules involving isocyanide-based multicomponent reactions. The majority of all reported syntheses employ the Ugi four-component reaction. The review also covers the Passerini and Groebke-Blackburn-Bienaymé reactions. To date, the main advantages of the solid-phase approach are the ability to prepare chemical libraries intended for biological screening and elimination of the isocyanide odor. However, the potential of multicomponent reactions has not been fully exploited. The unexplored avenues of these reactions, including chiral frameworks, DNA-encoded libraries, eco-friendly synthesis, and chiral auxiliary reactions, are briefly outlined.
Keywords: vztahy mezi strukturou a aktivitou; Drug Discovery; Solid-Phase Synthesis Techniques; Cyanides; Chemistry Techniques, Synthetic; techniky syntetické chemie; objevování léků; kyanidy; techniky syntézy na pevné fázi; Resins, Synthetic; Structure-Activity Relationship; syntetické pryskyřice